La extinción de la relación laboral por causas relacionadas con la capacidad del trabajador - Cadillo Ángeles, Carlos (Revista de Derecho, 2019)
The present article deals with the causes for the extinction of work relationship based on the affectation of the worker’s abilities: Permanent absolute handicap and dismissal related to ability. The latter gathers three postulations: deficiencies in the worker’s abilities, deficient performance, and refusal to undertake medical examinations or to comply with prophylactic or healing measures prescribed by the doctor with preventive aims. These are all issues of upmost importance which even when they justify the breaking of the work relationship, limit the worker’s work stability. In this regards, we develop the scope, requisites and formalities which should be met for a justified usage of such causal.